2019
DOI: 10.1002/ijc.32315
|View full text |Cite
|
Sign up to set email alerts
|

HPV73 a nonvaccine type causes cervical cancer

Abstract: HPV73 is classified as possibly oncogenic. It is neither routinely evaluated in HPV screening, nor covered by any of the prophylactic vaccines. We sought to investigate the carcinogenic characteristics of HPV73. Molecular studies were performed on eight cervix cancer biopsy specimens containing HPV73 from a cross‐sectional cancer cohort of 590 women referred to the National Cancer Institute in Rio de Janeiro, Brazil. Transcriptional activity of HPV73 was evaluated by detection of spliced transcripts of E6/E6* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
(54 reference statements)
2
29
1
1
Order By: Relevance
“…HPV73 was previously thought to be a LR type, but a recent report suggested that it can be identified in cervical cancer . Compared with the prevalence in CIN, HPV53 and HPV73 were more frequent in VAIN than in CIN in the present study (Figure C).…”
Section: Discussioncontrasting
confidence: 55%
“…HPV73 was previously thought to be a LR type, but a recent report suggested that it can be identified in cervical cancer . Compared with the prevalence in CIN, HPV53 and HPV73 were more frequent in VAIN than in CIN in the present study (Figure C).…”
Section: Discussioncontrasting
confidence: 55%
“…Nevertheless, this finding of a possible HPV 6 herd effect postbivalent HPV vaccination, is consistent with previous findings of bivalent vaccine efficacy against HPV6, 36 reported postvaccine era reductions in genital warts when using the bivalent vaccine, 37,38 and also with findings of HPV6 specific vaccine-induced cross-neutralising antibodies among individuals vaccinated with the bivalent HPV vaccine. 35 39 HPV73 is from the alpha 11 species group, which is of particular interest given that the alpha 11 species group is phylogenetically close to the alpha 9 species, and the degree of cross-protection is correlated to the phylogenetic distance to the vaccine types. 40 Contrary to this, the observed decrease of HPV66 in Arm A was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since 2007, these vaccines have been gradually implemented in national vaccination programs. 3 However, there are a total of 12 high-risk HPV types which are classified by the International Agency for Research on Cancer (IARC) as carcinogenic to humans, HPV16, 18,31,33,35,39,45,51,52, 56, 58 and 59, with a further eight types classified as possibly (or probably) carcinogenic, HPV26, 53, 66, 68, 67, 70, 73 and 83. 4 As such, concern has been flagged over a decade ago, whether such selective vaccination could induce HPV type replacement to occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is limited epidemiological data on the occurrence of HPV69 and HPV73 worldwide. This phenomenon may be explained by regional variability in the prevalence of HPV oncogenic types [15], as well as by variable performance of current detection and typing methods, which are generally designed to screen for the most common high-risk human-associated HPV genotypes [1].…”
Section: Discussionmentioning
confidence: 99%